Different of Cholesterol Levels in Cigarette Smokers and Electronic Cigarette - Norma Farizah Fahmi; Sitti Zahratul Uyuni (Biomedika, 2020)
Smoking causes an increase in cholesterol in the blood. It is well known that tobacco contains nicotine has a considerable influence on the increase of blood lipid levels. Normally, lipids play an important role in all aspects of biological life, but excessive cholesterol causes changes in lipid composition, induces ROS formation and lipid oxidation. This process can also cause damage to proteins and DNA, changing cellular function, which causes tissue damage. This research using analytic survey, with analytic cross sectional design with 30 subjects. The mean cholesterol level between tobacco smokers is 210.0 mg / dl and electric smokers is 123.73 mg / dl. The average difference in cholesterol levels among smokers was tested using One way ANOVA, p value = 0.000 (p <0.05). The cholesterol level of the tobacco smoker group was significantly higher when compared to the electronic smoker group.